Distributed and accumulated reinforcement arrangements: Evaluations of efficacy and preference. Issue 2 (30th April 2014) - DeLeon, Iser G.; Chase, Julie A.; Frank‐Crawford, Michelle A.; Carreau‐Webster, Abbey B.; Triggs, Mandy M.; Bullock, Christopher E.; Jennett, Heather K.
Abstract We assessed the efficacy of, and preference for, accumulated access to reinforcers, which allows uninterrupted engagement with the reinforcers but imposes an inherent delay required to first complete the task. Experiment 1 compared rates of task completion in 4 individuals who had been diagnosed with intellectual disabilities when reinforcement was distributed (i.e., 30‐s access to the reinforcer delivered immediately after each response) and accumulated (i.e., 5‐min access to the reinforcer after completion of multiple consecutive responses). Accumulated reinforcement produced response rates that equaled or exceeded rates during distributed reinforcement for 3 participants. Experiment 2 used a concurrent‐chains schedule to examine preferences for each arrangement. All participants preferred delayed, accumulated access when the reinforcer was an activity. Three participants also preferred accumulated access to edible reinforcers. The collective results suggest that, despite the inherent delay, accumulated reinforcement is just as effective and is often preferred by learners over distributed reinforcement.